Peritraumatic distress and demographic characteristics among practicing Peruvian dentists during the COVID-19 pandemic: a cross sectional study - Arroyo-Ortiz, Gustavo (2025)
Objective. To determine the relationship between the presence of peritraumatic distress associated with the COVID-19 pandemic and demographic characteristics in dentists from Lima and Callao - Peru in 2021. Materials and methods. Cross-sectional study of 236 participants who responded to a virtual survey between June and November 2021. The social characteristics of the dentists were recorded and a translated, adapted and validated version of the COVID-19 Peritraumatic Distress Index (CPDI) questionnaire was used. For bivariate analysis, the chi-square test was used. Results. The mean peritraumatic distress score was 25.46 (±12.401). Almost 59.7 % of the participants were free of distress, while 38.1% experienced mild to moderate symptoms and 2.1 % had severe distress. Women experienced a significantly higher level of psychological distress than men (p < 0.003) and a statistically significant relationship was observed between distress and weekly work hours before the pandemic (p < 0.012). Conclusions: More than a third of the participants exhibited mild to moderate peritraumatic distress, while more than half did not report any clinical manifestation, even after more than a year and a half of the pandemia’s onset. Finally, identifying and analyzing associated factors and vulnerable groups facilitate the promotion of strategies to prevent and mitigate their impact, with the aim of protecting the psychological well-being of dentists in the face of future health emergencies.